AMPK as a New Attractive Therapeutic Target for Disease Prevention: The Role of Dietary Compounds AMPK and Disease Prevention - Gasparrini, Massimiliano; Giampieri, Francesca; M. Alvarez Suarez, Josè; Mazzoni, Luca; Y. Forbes Hernandez, Tamara; L. Quiles, Josè; Bullon, Pedro; Battino, Maurizio (Current Drug Targets, 2016)
AMPK is a serine/threonine protein kinase that has the function of maintaining the balance between ATP production and consumption in most eukaryotic cells. It plays a relevant role in regulating cellular metabolism, preserving cellular energy homeostasis, and is involved in many other cellular processes as well as metabolic ones, including cell cycle regulation and endothelial and vascular relaxation. Recently, the effects of naturally occurring compounds able to prevent and treat diseases through AMPK activation have attracted the attention of many researchers. Among such compounds, flavonoids found in natural sources, like quercetin, genistein, epigallocatechins, resveratrol, have been proposed as AMPK activators. This review summarizes and updates the most recent findings concerning the mechanisms through which different dietary compounds, from plant foods, affect the AMPK pathway in healthy and pathological in vitro and in vivo models, paying particular attention to molecular mechanisms involved in diabetes, obesity, metabolic syndrome, cardiovascular disease and cancer.
Keywords: Coenzyme Q